Estimating household;s willingness to pay for improved water quality through the implementation of the wastewater collection and treatment system in Poblacion, Davao City - Mitchor, April N.
This study intended to estimate household's willingness to pay for the implementation of the wastewater collection and treatment system in Poblacion, Davao City. Specifically, the study aimed to identify and assess the various factors which affect the person's willingness to pay. WTP bids were elicited through the use of the contingent valuation method. A survey was conducted to 50 randomly selected respondents in the Poblacion area of the city. The use of the CVM in estimating household' WTP for wastewater collection and treatment service worked quite well in this study. Relatively large number of respondents revealed positive WTP bids with an average Php67.60 monthly fee. Assuming that the same value holds true for the other people or households in the whole of Poblacion as well as the other two service areas of the project which are Agdao and Talomo, approximately Php47,493,326.40 annual revenue can be generated by the local government in the three service areas. However, this figure is inadequate to finance the annual operating expenses of the project thus, the need for the local government to exert effort in finding alternatives in raising funds to support the project. Results of the study can help the local government in assessing the economic viability of implementing wastewater collection and treatment services fee among households.